2000
DOI: 10.1023/a:1009271221684
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Copper(II) alpha,omega-dicarboxylate complexes of general formulae, [Cu(O2C(CH2)nCO2)].xH2O, [Cu(O2C(CH2)nCO2) (phen)2].xH2O and [Cu(O2C(CH2),CO2)(bipy)y].xH2O (n = 1-8; y = 1, 2; phen = 1,10-phenanthroline; bipy = 2,2'-bipyridine) were synthesised. These copper complexes, some related manganese(II) complexes and the metal-free ligands were screened in vitro for their ability to inhibit the growth of Candida albicans. Metal-free 1,10-phenanthroline and all of the copper(II) and manganese(II) phenanthroline com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…23 In addition, the present study has shown that the simple metal malonates (metal Mn(II), Co(II), Ni(II), Cu(II), Zn(II)) and Ni(CH3CO2)2.4H20 also have negligible activity against the yeast.…”
Section: Resultsmentioning
confidence: 60%
“…23 In addition, the present study has shown that the simple metal malonates (metal Mn(II), Co(II), Ni(II), Cu(II), Zn(II)) and Ni(CH3CO2)2.4H20 also have negligible activity against the yeast.…”
Section: Resultsmentioning
confidence: 60%
“…Acrylonitrile (3.6 g, 67 mmol) was added to a mixture of 2-BIM (5.0 g, 34 mmol), and triethylamine (6.8 g, 67 mmol) in acetonitrile (150 cm 3 ). The reaction mixture was refluxed with stirring for 5 h. The solvent was removed under reduced pressure giving a white solid, which was recrystallised from acetone.…”
Section: -Bim(cn)mentioning
confidence: 99%
“…In our efforts to develop new metal complexes that would greatly inhibit the growth of the human fungal pathogen Candida albicans [1][2][3][4] we have found that, to date, the most active drug tested in aqueous media is the Ag(I) complex [Ag(phendio) 2 ]ClO 4 (phendio ¼ 1,10-phenanthroline-5,6-dione) [5]. As part of these ongoing studies into the synthesis and in vitro testing of new metalbased anti-fungal drugs we report here the preparation of five Ag(I) complexes containing bis(imidazole) ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that a range of carboxylate and dicarboxylate complexes incorporating transition metal centres and including the N,N 0 -donor ligand 1,10-phenanthroline (phen) are potent in vitro inhibitors of the growth of C. albicans [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%